2014
DOI: 10.1111/ijsa.12075
|View full text |Cite
|
Sign up to set email alerts
|

The General Factor of Personality (GFP) Relates to Other Ratings of Character and Integrity: Two validity studies in personnel selection and training of the Dutch armed forces

Abstract: In two studies, we tested whether scores on the general factor of personality (GFP) are associated with other ratings of character and integrity. In Study 1, a total of 3,670 applicants for a military job filled out personality surveys and went through a selection interview. GFPs extracted from two different personality surveys showed meaningful relationships with the job suitability judgments based on the interviews. In Study 2, supervisors rated the integrity of participants (N = 167) who followed a 4-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…In defense of the substantive status of a GFP, twin studies have shown it to be substantially heritable (Loehlin & Martin, 2011; Veselka et al, 2009), and to show relationships with measures of social effectiveness and ratings of character and integrity (Dunkel & van der Linden, 2014; van der Linden et al, 2014). Rushton et al (2008) proposed an evolutionary origin of the GFP: namely, that it was a result of selection on a set of traits contributing to social effectiveness and thus to reproductive success.…”
mentioning
confidence: 99%
“…In defense of the substantive status of a GFP, twin studies have shown it to be substantially heritable (Loehlin & Martin, 2011; Veselka et al, 2009), and to show relationships with measures of social effectiveness and ratings of character and integrity (Dunkel & van der Linden, 2014; van der Linden et al, 2014). Rushton et al (2008) proposed an evolutionary origin of the GFP: namely, that it was a result of selection on a set of traits contributing to social effectiveness and thus to reproductive success.…”
mentioning
confidence: 99%
“…This is also referred to as the D factor in dark traits. Previous studies have examined the direct correlations between the core of the Dark Triad and the GFP (Kowalski et al, 2016;Van der Linden et al, 2014).…”
Section: Ego-resiliencementioning
confidence: 99%
“…In a large meta-analysis, van der Linden et al ( 2017 ) showed that the GFP has almost complete overlap (ρ = 0.88) with trait emotional intelligence and moderate associations (ρ = 0.28) with ability emotional intelligence. A second line of evidence shows that the GFP relates to various criteria of social success, including peer-rated likeability and popularity and higher ratings on several objective socio-economic performance indicators (van der Linden et al, 2010b , 2014a , b ). Those findings are in accordance with the view that the GFP does not merely reflect bias, but instead arise because high-GFP individuals genuinely tend to behave in a more socially desirable manner, while low GFP scores would be associated with problematic social behavior, including violence, delinquency, and impulsive sensation-seeking.…”
Section: The Gfp Reflecting Social Effectivenessmentioning
confidence: 99%